Management of Postoperative Pancreatic Fluid Collection and Role of Endoscopy: A Case Series and Review of the Literature - Chiara Coluccio; Ilaria Tarantino; Maria Chiara Petrone; Edoardo Forti; Stefano Francesco Crinò; Alessandro Fugazza; Roberto Di Mitri; Cecilia Binda; Davide Trama; Arnaldo Amato; Alessandro Redaelli; Germana De Nucci; et al. (Diagnostics)
Background: Postoperative fluid collections (POFCs) after abdominal surgeries, particularly pancreatic surgeries, are associated with high morbidity and mortality rates and were historically managed with surgical re-exploration and drainage. In particular, postoperative pancreatic fluid collections (PPFCs) are the most common complications after pancreatic surgery resulting from pancreatic leaks. They occur in up to 50% of cases, and approximately 10% of them need to be drained to avoid further sequelae. Endoscopic ultrasonography (EUS)-guided drainage of PPFCs represents the first-line treatment nowadays, but many aspects are still debated. Methods: We describe a retrospective case series of patients from multiple Italian centers who underwent EUS-guided drainage (EUS-D) of POFCs, aiming to provide data on the efficacy and safety of this procedure, supported by a review of the existing literature on this topic. The primary outcomes were technical and clinical success, and the secondary outcomes were the type and rate of adverse events (AEs) and the rate of recurrence. Results: A total of 47 patients were included. The procedure demonstrated a technical success rate of 98% (46/47) and a clinical success rate of 96% (45/47). The rate of AEs was 11% (5/47), represented by bleeding (3/5), stent occlusion (1/5), and buried syndrome (1/5). Conclusions: Management of POFCs has shifted over time towards an endoscopic approach with optimal efficacy and safety.